Հովհաննես գրչապետի աշխատասիրած «Համառաւտ Աստուածաշունչ» ձեռագրերի (CBL551 և Մ10772) աղբյուրագիտական հենքը - Սարգսյան, Անուշ («Նաիրի» հրատ.)
Среди работ иерея Ованнеса, одного из самых знаменитых рукописцев амидской школы XVII века, особняком стоят две однотипные рукописи, CBL551 и М10772. Их текст является генеалогическим древом и списком последовательности правителей в библейской истории, при этом важнeйшее место уделено генеалогии Христа. Арборальные и иные таблицы придают материалу наглядность, и к ним прилагаются тексты с объяснениями. Особенности рукописей в основном обусловлены систематизированным строением древа, изобразительными элементами и разнообразными украшениями текста, а также вертикальным использованием пространства, а в случае CBL551 – форматом книги-аккордеона. A specific place among the works of priest Yohannes, one of the most famous scribes of the XVII century Amid school of writing, belongs to two similar manuscripts, CBL551 and M10772. Their text comprises the genealogy and a list of succession of rulers in the Biblical history, in which the most important place is reserved for the genealogy of Christ. Trees and other diagrams visualize the material, and the texts attached to them contain explanations. Specific features of the manuscripts are: the systematized structure of the tree, pictorial elements and various ornamentation of the text, as well as the vertical use of the writing space, in case of CBL551 it is also the accordion book format.
Keywords: Արվեստ; Ձեռագրարվեստ